Towards achieving the quality of life in the management of zakat distribution to the rightful recipients (the poor and needy) - Abu Bakar, Mahyuddin; Abdul Ghani, Abdullah (Center for Promoting Ideas (CPI), USA, 2011)
Zakat is an Islamic institution anchored within the Islamic economic system to cater for the Muslims’ social welfare. One of the primary objectives of zakat is to eradicate poverty among Muslims. Furthermore, the institution of zakat has been given the responsibility to ensure that the rightful recipients (the asnaf), mainly the poor and needy could attain a minimum quality of life from the zakat received. To ensure that such quality of life is possible, a more proactive mechanism for zakat distribution is a must.The form of mechanism could come in the form of monetary capital and equipment to help recipients improve their standard of living.The premise for this research is that a more self-sustained mechanism of zakat distribution could become the most effective tool that guarantees better quality of life for the beneficiaries.The maslahah approach introduced by al Ghazali and al Syatibi will dictate the level of minimum standard of living for the poor and needy. The measurement for wellbeing (al hajiyyat) which is the minimum standard for quality of life is in tandem with Maslow’s human development theory which posits the level of comfort living as a quality living for people in general. In relation to this, the Maqasid al Syariah in zakat jurisprudence will be achieved if the recipient views the gift of zakat as benefitting them when they attain the level of comfort in their life.